1986
DOI: 10.1002/aja.1001750406
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐ and postnatal development of heterogeneity in the amounts of endoplasmic reticulum in mouse hepatocytes

Abstract: The surface density and area per cell of the endoplasmic reticulum (ER) in periportal and perihepatic hepatocytes from male ddY mice, "17-, 18-, and 19-day-old fetuses," "newborn and 1-, 5-, 10-, and 20-day-old animals," and "adult animals" were analyzed by quantitative electron microscopy. The surface density of rough ER was not significantly different between periportal and perihepatic cells in all age groups examined, except for 19-day-old fetuses in which the value was greater in periportal cells than peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…This possibility is a matter for future studies. Interestingly, the ontogenic expression of hepatic AQP8 also coincides with the hormonally controlled maturation of the mouse hepatocyte SER.32, 49 The mouse liver AQP9 has recently been shown to be regulated at a transcriptional level coordinately by the plasma concentrations of insulin in accordance with the nutritional condition, such as fasting and refeeding. Whether SER AQPS is regulated by hormones controlling the metabolism of hepatic glucose is an exciting matter for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is a matter for future studies. Interestingly, the ontogenic expression of hepatic AQP8 also coincides with the hormonally controlled maturation of the mouse hepatocyte SER.32, 49 The mouse liver AQP9 has recently been shown to be regulated at a transcriptional level coordinately by the plasma concentrations of insulin in accordance with the nutritional condition, such as fasting and refeeding. Whether SER AQPS is regulated by hormones controlling the metabolism of hepatic glucose is an exciting matter for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not distinguish between periportal and perivenular hepatocytes. Kanai et al (1986a) found that the area of SER per unit cytoplasmic volume increases only slightly in periportal hepatocytes between 17-day-old fetuses and adult mice (Fig. 4).…”
Section: Sermentioning
confidence: 90%
“…Kanai et al (1986a) observed that the area of RER per unit cytoplasmic volume does not change in either periportal and perifollowing a n overnight mating. (Reproduced from Kanai et al, 1986a, with permission of the publisher.) venular hepatocytes during development except (1) just before birth and (2) between 20 days of age and adulthood (Fig.…”
Section: Hepatocyteorganelles Rer and Golgi Complexmentioning
confidence: 96%
See 1 more Smart Citation
“…The typical adult pattern of predominantly one cell thickness is not established in the human until about five years of age in the child (Morgan & Hartort 1961;Macsween 1994). During the postnatal period, there are also increases in hepatocyte size, average diameter hepatic lobules and quantity of endoplasmic reticulum (Kanai et al 1986;Kanamura et al 1990;Macsween 1994). Sinusoidal fenestrations increase in density in the early postnatal period, coincident with the establishment of zonation of hepatocellular metabolic activity within the acinus (Barbera-Guillem et al 1986).…”
Section: Hepatic Physiologymentioning
confidence: 99%